Risk mitigation strategies of multinational corporations (MNCs) amid great power rivalry - Bekzod Rajabov (Nanyang Technological University, 2020)
This thesis explores the risks mitigation strategies of Multinational corporations (MNC) amid the trade war and technological competition between the US and China. As this economic rivalry intensifies, MNCs face increased risks due to the uncertainty of political disruption that has replaced the decades-long neoliberal trade policies. However, the existing theories on political risk overlook the risks from the great power rivalry. Therefore, the thesis develops a conceptual framework based on sanctions corporate risk management strategies involving “Compliance,” “Lobbying,” and “Joint Ventures.” Then, empirically, the thesis examines three technological MNCs; Apple Inc, Huawei, and Samsung Electronics using the conceptual framework. First, the thesis determines the corporate market exposure level by looking at headquarters, primary markets, and operations of these MNCs. Then, the thesis studies the main risk factor the respective MNC facing amid the economic and technological competition between the US and China. Having established that, the thesis finds that American based Apple Inc. has chosen the lobbying as a risk mitigation strategy. Huawei, on the other hand, receiving a relatively small share of revenues from the US market, chooses the complying strategy as the company lacks other options. Samsung, based in South Korea, faces significant risks both to its markets and operations. Therefore, adopting a country-based approach, Samsung chooses Joint Ventures strategy in China to mitigate risks. The findings in this thesis not only provides a broad introduction to the political risk amid great power rivalry, but it also offers policymakers a necessary understanding of corporate risk management strategies.